Cemetery spaces a locus for tourist activity: the potential of the Campo Santo cemetery in Salvador (BA) (Research, Society and Development, 2020)
Cemeteries or necropolises are important cultural sites in cities, both for their symbolic value in terms of the expression of memory and religiosity and for their influence on the landscape. This study covers the formation process of the first necropolises and the paths that contributed to the conception of the cemetery model adopted at the present time. Added to this, the analysis of the practices and habits that conceived these important cultural sites, the symbolic value present in the memory, in the religiosity and in the architectural landscape of cities and societies. The objective is to contribute to the discussions that deal with non-traditional spaces with great potential for tourist attraction, in this case, the funerary cultural heritage glimpsing in the cemeteries. The methodology adopted included the bibliographic review and critical analysis of the main theorists on the theme, seeking to relate aspects about visitation and tourism in cemeteries. The empirical object of the study was the Campo Santo Cemetery, one of the main cemeteries located in the tourist city of Salvador-BA. It is observed in the research, that cemetery tourism, like what happened in Campo Santo, appears as a possibility of exploring an urban space full of symbolism and cultural appeal, expanding the range of tourist attractions in the capital of Bahia.